Relaxation of the bulk modulus in partially molten dunite?. Issue 22 (26th November 2016) - Cline, C. J.; Jackson, I.
Abstract: To address the possibility of melt‐related bulk modulus relaxation, a forced oscillation experiment was conducted at seismic frequencies on a partially molten synthetic dunite specimen (melt fraction = 0.026) utilizing the enhanced capacity of the Australian National University attenuation apparatus to operate in both torsional and flexural oscillation modes. Shear modulus and dissipation data are consistent with those for melt‐bearing olivine specimens previously tested in torsion, with a pronounced dissipation peak superimposed on high‐temperature background. Flexural data exhibit a monotonic decrease in complex Young's modulus with increasing temperature under transsolidus temperatures. The observed variation of Young's modulus is well described by the relationship 1/ E  ~ 1/3 G, without requiring relaxation of the bulk modulus. At high homologous temperatures, when shear modulus is low, extensional and flexural oscillation measurements have little resolution of bulk modulus, and thus, only pressure oscillation measurements can definitively constrain bulk properties at these conditions. Key Points: An "attenuation" apparatus has been modified to allow both torsional and flexural oscillation measurements under common P‐T conditions Reduction of Young's modulus with increasing temperature can be reconciled with shear data, without invoking bulk relaxation Flexural and extensional measurements at high homologous temperature provide little resolution of bulk modulus